Quasistatic Load Sharing Behaviours of Concentric Torque-Split Face Gear Transmission with Flexible Face Gear. (6th November 2018) - Zhao, Ning; Li, Wang; Hu, Tao; Guo, Hui; Zhou, Ruchuan; Peng, Yanjun
Abstract : The concentric torque-split face gear transmission is mainly developed for the rotorcraft which demands high power density and large speed reduction ratio. This paper aims at predicting the load sharing behaviours among paths. An original quasistatic load sharing analysis model, which is a hybrid finite element/lumped parameter quasistatic gear model, is presented. The connection between spur gear and face gear is also established. A number of numerical simulations of load sharing behaviour analysis are conducted. The mechanism of uneven load sharing is revealed. It is observed that the support stiffness of pinion and backlash have significant influences on the load sharing behaviours of the concentric torque-split face gear transmission.